INOVASI PENDIDIKAN BERBASIS TEKNOLOGI DIGITAL DALAM MENINGKATKAN KUALITAS PEMBELAJARAN DI ERA SOCIETY 5.0 - Sri Utami; Asmunik; Agus Tinus (Berajah Journal, 2026)
The era of Society 5.0 demands the integration of digital technology in various aspects of life, including education. This study aims to analyze digital technology-based educational innovations in improving the quality of learning. The method used is a literature review with a descriptive qualitative approach based on various journals, books, and research reports. The results indicate that the use of digital technologies such as Learning Management Systems (LMS), artificial intelligence, and interactive learning media can enhance student engagement, learning effectiveness, and learning outcomes. However, challenges such as the digital divide, teacher competence, and limited infrastructure remain major obstacles. Therefore, a comprehensive implementation strategy is required to maximize the use of technology in education.